Analysis and modeling of Internet backbone traffic with 5G/B5G - Yuan YANG; Mingwei XU; Hao CHEN (Tongxin xuebao)
The effects that the 5th generation mobile network (5G) bring to Internet backbone were investigated qualitatively and quantitatively.First,the challenges that the characteristics of 5G,i.e.ultra-high data rate,ultra-low latency,and ultra-large number of connections,introduce to Internet backbone in terms of traffic,latency,and security were analyzed.Second,a model was proposed to capture the characteristics of 5G users and Internet traffic with the coordination of 5G,edge computing,and cloud computing.Then,numerical simulations were used to evaluate the model.The QoS requirements that Internet backbone faces under different extent of 5G deployment were evaluated.According to the study,increment of backbone traffic,increment of the ratio of propagation delay,and movement of bandwidth bottleneck are predicted after 5G/B5G deployment.